Managing bone loss in open fractures. Issue 1 (March 2020) - Adamczyk, Andrew; Meulenkamp, Bradley; Wilken, Geoffrey; Papp, Steven
Abstract : Abstract: Segmental bone loss continues to pose substantial clinical and technical challenges to orthopaedic surgeons. While several surgical options exist for the treatment of these complex patients, there is not a clear consensus or specific guidelines on the optimal management of these injuries as a whole. Many factors must be taken into consideration when planning surgery for these individuals. In order for these techniques to yield optimal results, each injury must be approached in a step-wise and multidisciplinary fashion to ensure that care is taken in bone and wound bed preparation, that soft tissues are healthy and free of contaminants, and that the patient's medical condition has been optimized. Through this article, we will answer relevant questions and discuss common obstacles and challenges encountered with these complex injuries. We will also review the many treatment options available or in development to address this problem.